Development of a research design module for industry professionals: a pilot study / Dr. Maisarah Ahmad Kamil, Nadia Anuar and Zulaikha Khairuddin - Ahmad Kamil, Maisarah; Anuar, Nadia; Khairuddin, Zulaikha (Universiti Teknologi MARA, Kedah, 2024)
This study presents a research design module that was developed for and piloted with industry professionals who are new to research. This module aims to enhance their understanding of social science research methods applicable to organizational contexts. The module consisted of three topics, two alignment templates, and two live quizzes to clarify and align their research components. At the beginning of the training, an open-ended question was posed to identify the challenges in their research endeavors. Another question was asked at the end of the module to determine the impact of the intervention. The feedback showed that the participants valued the proposed innovative alignment templates and found the training to be invaluable in enhancing their knowledge of research design. The interactive nature of the module also facilitated them in acquiring a deeper understanding of research concepts application in their organization. The results prove the value of the proposed module for industry professionals who are new to research. Based on the feedback, several changes to the module should be made to enhance its effectiveness in the future, including incorporating more case studies and examples relevant to diverse research contexts.